RELEVANCE OF BAHASA INDONESIA MAIN MATERIALS WITH HOTS (HIGHER ORDER THINKING SKILLS) - Rahmi, Rina; Nurhalizha, Iin; Nabila, Nasrin (UIN Sunan Kalijaga Yogyakarta, 2020)
This article aims to analyze the relevance of Bahasa Indonesian subject matter revised of 2017 Integrated Thematic book for Grade IV at semester one published by the Ministry of Education and Culture (MOEC) with High Order Thinking Skills (HOTS). This research was conducted because HOTS is one of the necessary skills in the 21st century so that the material of Bahasa Indonesian subject matter in the thematic teaching book must be relevant to HOTS because the teaching material is one aspect that affects the implementation of learning activities. A descriptive qualitative was applied to conduct this study. The primary data source was Thematic Books (both for teacher and student) for semester one at Grade IV of primary school. Data were analyzed using a content analysis based on Bloom's taxonomy theory because the theory makes the level of human thinking level from the lowest to the highest. The results showed 27 indicators that contain HOTS, which are five indicators in theme 1, 3 indicators in theme 2, 6 indicators in theme 3, 8 indicators in theme 4, and 5 indicators in theme 5. Bahasa Indonesian subject matter contained in the integrated Grade IV of Revision 2017 published by Kementerian Pendidikan dan Kebudayaan is relevant to HOTS.